Coarctation of the aorta, interrupted aortic arch, and hypoplastic left heart syndrome in three generations. Issue 4 (April 1993) - Gerboni, S; Sabatino, G; Mingarelli, R; Dallapiccola, B
Abstract : Five members in three generations of a family were affected by a congenital heart disease. Four of them had mild or severe coarctation of the aorta (CoA), either isolated or in association with other cardiac defects. Fetal echocardiography allowed prenatal diagnosis in one pregnancy at risk. This family suggests that a rare form of CoA could be the result of an autosomal dominant mutation with high penetrance and variable expressivity rather than polygenic inheritance.